Angiogenic factors: potential to change clinical practice in pre-eclampsia? - Cerdeira, A; Agrawal, S; Staff, A; Redman, C; Vatish, M (John Wiley & Sons Ltd, 2017)
Preeclampsia is a complex disease with significant maternal and fetal morbidity and mortality. Its syndromic nature makes diagnosis and management difficult. The field is rapidly evolving with the definition of preeclampsia being challenged by some organizations with proteinuria no longer being essential in the presence of other features. In the last decade angiogenic factors, in particular soluble fms-like tyrosine kinase 1 (sFlt-1), have emerged as important molecules in the pathogenesis of preeclampsia. Here we review the most recent evidence regarding the potential of these factors as biomarkers and therapeutic targets for preeclampsia. This article is protected by copyright. All rights reserved.